Low‐Bandgap Methylammonium‐Rubidium Cation Sn‐Rich Perovskites for Efficient Ultraviolet–Visible–Near Infrared Photodetectors. (18th January 2018) - Zhu, Hugh Lu; Liang, Zhifu; Huo, Zhengbao; Ng, Wai Kit; Mao, Jian; Wong, Kam Sing; Yin, Wan‐Jian; Choy, Wallace C. H.
Abstract: Solution‐processed and low‐temperature Sn‐rich perovskites show their low bandgap of about 1.2 eV, enabling potential applications in next‐generation cost‐effective ultraviolet (UV)–visible (vis)–near infrared (NIR) photodetection. Particularly, the crystallization (crystallinity and orientation) and film (smooth and dense film) properties of Sn‐rich perovskites are critical for efficient photodetectors, but are limitedly studied. Here, controllable crystallization for growing high‐quality films with the improvements of increased crystallinity and strengthened preferred orientation through a introducing rubidium cation into the methylammonium Sn‐Pb perovskite system (65% Sn) is achieved. Fundamentally, the theoretical results show that rubidium incorporation causes lower surface energy of (110) plane, facilitating growth in the dominating plane and suppressing growth of other competing planes. Consequently, the methylammonium‐rubidium Sn‐Pb perovskite photodetectors simultaneously achieve larger photocurrent and lower noise current. Finally, highly efficient UV–vis–NIR (300–1100 nm) photodetectors with record‐high linear dynamic range of 110 and 3 dB cut‐off frequency reaching 1 MHz are demonstrated. This work contributes to enriching the cation selection in Sn‐Pb perovskite systems and offering a promising candidate for low‐cost UV–vis–NIR photodetection. Abstract : Controllable crystallization for growing high‐quality films with increased crystallinity and strengthened preferred orientation is achieved through introducing rubidium cation into the methylammonium Sn‐Pb perovskite system. Methylammonium‐rubidium Sn‐rich perovskite‐photodetectors simultaneously achieve larger photocurrent and lower noise current. Highly efficient UV–vis‐near infrared (300–1100 nm) photodetectors with record‐high linear dynamic range of 110 and 3 dB cut‐off frequency reaching 1 MHz are demonstrated.